The Development of Thai Language Activity Set on Spelling Rules Using 5E Inquiry-Based Learning for Prathomsuksa 2 Students in The Primary Educational Service Area Office Bangkok, Chom Thong District - Mapradit, Thanwa; Wongsan, Weera; Hunsuwan, Kannaphat (Journal of Education Rajabhat Maha Sarakham University, 2024)
The purposes of this research were: 1) to develop a Thai language activity set on spelling rules using 5E inquiry-based learning for Prathomsuksa 2 students to meet the specified criteria of 80/80, 2) to study the effectiveness of the Thai language activity set on spelling rules using 5E inquiry-based learning for Prathomsuksa 2 students, 3) to compare the Thai language learning achievement on spelling rules of Prathomsuksa 2 students in 5E inquiry-based learning and traditional learning and 4) to compare the satisfaction on the activity set of Prathomsuksa 2 students in 5Es inquiry-based learning and traditional learning. The sample group consisted of 34 Prathomsuksa 2 students at Anubanwatnangnong School. The research tools were Thai language activity set on spelling rules, Thai language lesson plans, Thai language learning achievement test and student satisfaction questionnaire. The data analysis statistics included percentage, mean, standard deviation and Dependent Sample t-test. The research results found that: 1) Efficiency of the Thai language activity set for Prathomsuksa 2 students had E1/E2 value of 86.10/80.88, which is higher than the specified criteria, 2) the effectiveness of the Thai language activity set revealed the Effectiveness Index (E.I.) of 0.67, 3) Prathomsuksa 2 students in 5Es inquiry-based learning had learning achievement higher than students in traditional learning at statistical significance level of .01 and 4) Prathomsuksa 2 students in 5Es inquiry-based learning had overall satisfied higher than students in traditional learning at statistical significance level of .01.